Translanguaging Used in Speaking Class of Non-Formal Education Program: Students’ and Teachers’ Perceptions - Tristin Puspitasari, Pratiwi; Sugirin, Sugirin (EDUPEDIA Publisher, 2024)
The idea that Kampung Inggris, Pare, Kediri's English as a Foreign Language (EFL) teachers employed translanguaging activities as a strategy to help students perform better in speaking classes. This study investigated the views of teachers and students toward the use of translanguaging in the classroom. The study's primary focus was on the teacher's and student’s knowledge and experiences with translanguaging in EFL classroom interactions. The study involved two participants, an English language program student and a teacher from Kampung Inggris, Pare, Kediri. The words spoken during the teacher and student interviews were described qualitatively through depth interviews and observation. The findings indicated that although the EFL teacher had no prior knowledge of translanguaging, she had nonetheless employed it in the teaching and learning process. As a result, student’s understood what translanguaging was. Both of them think they know a lot about the translanguaging process. In line with them, translanguaging is the use of both Indonesian, Javaness and English in an ELT classroom—creates a secure environment for student engagement, enhances and promotes student's comprehension of the course material, and acts as an approach for information transfer. In ELT classes, teachers of English as a foreign language are already skilled at applying translanguaging techniques. Students who asked and responded to questions received rewards, in addition to the use of translation to facilitate students' understanding of new materials or themes. As English is spoken less frequently than Indonesian, it will also be harder for students to meet their learning objectives for speaking English